Pro Java ME apps building commercial quality Java ME apps - Iliescu, Ovidiu (Apress, 2011)
Pro Java ME Apps gives you, the developer, the know-how required for writing sophisticated Java ME applications and for taking advantage of this huge potential market. Java ME is the largest mobile software platform in the world, supported by over 80% of all phones. You'll cover what Java ME is and how it compares to other mobile software platforms, how to properly design and structure Java ME applications, how to think like an experienced Java ME developer, what common problems and pitfalls you may run into, how to optimize your code, and many other key topics.  Unlike other Java ME books out there, which only teach the reader the basics of Java ME by way of a few simple examples, this book presents a broader, eagle-eye picture of a complete Java ME application and what writing one involves. From there, the book presents, explains, and helps you to implement all the essential aspects of Java ME development, from the user interface to client-server communication. As this unfolds, the decisions and reasoning behind the code are also presented. The book assumes that the reader is already familiar with Java ME and Java applications in general. Based on and geared towards real-life Java ME scenarios Guides the reader through the entire process of developing a high-quality Java ME application Explains the decisions made at each step, gives advice and examples of good practices vs. bad practices